Community based cross sectional study: to assess the prevalence of arthritic symptoms in an army garrison in large city of North India - Singh, Archana; Rastogi, Vineet; Sharma, Ridhima; Chaturvedi, Ved; Kotwal, Atul (International Journal of Research in Medical Sciences, 2020)
Background: Arthritis affects almost 350 million people globally and is one of the leading causes of disability in the world. The prevalence in India is like that in developed countries. Symptoms of arthritis have been found to be influenced by alcohol intake, smoking, obesity and type of diet which lead to aggravation in pain, exacerbation in disease activity and deterioration in general health. Methods: Present community-based cross-sectional study was conducted in a large military station in North India over a period of one month. Armed Forces personnel and their family members aged 18 yrs and above residing in military station and consenting to the study were included. A sample of 1475 was studied. Results: The age of participants ranged from 18 to 70 yrs (median 32±7.4 yrs) with 20.54% females and 79.46% males. The prevalence of symptoms suggestive of Gout, RA, OA and Spondyloarthritis was 8.95% (95% CI, 7.54, 10.52), 3.25% (2.41, 4.29), 11.32% (9.75, 13.05) and 14.17% (12.43, 16.05), respectively. Symptoms suggestive of RA were found to be significantly associated with female gender, those of Gout and Spondyloarthritis with male gender, while OA did not have any gender predisposition. Conclusions: The population with symptoms of arthritis needs to be identified early by early symptomatic diagnosis and measures instituted for appropriate management to prevent future complications and associated morbidity.